Immigrants' tolerance and integration into society - Niclas Berggren; Martin Ljunge; Therese Nilsson (Research Institute of Industrial Economics (IFN), 2022)
We highlight a new factor behind integration: tolerance in the immigrants' background culture. We hypothesize that it is easier to partake of economic, civic-political, and social life in a new country for a person stemming from a culture that embodies tolerance towards people who are different. We test this by applying the epidemiological method, using a tolerance index based on two indicators from the World Values Survey - the share that thinks it important to teach children tolerance and the share that considers homosexuality justified - as our main independent variable. Our outcomes are indices of individual-level economic, civic-political, and cultural integration outcomes for immigrants of the second generation with data from the European Social Survey. The results indicate that tolerance in the background culture is a robust predictor of integration among children of immigrants in European societies.
Keywords: F22; F66; J15; Z13; Z18; 330; Tolerance; Culture; Immigration; Integration; Values